2015
DOI: 10.3389/fpls.2015.00128
|View full text |Cite
|
Sign up to set email alerts
|

Proteome readjustments in the apoplastic space of Arabidopsis thaliana ggt1 mutant leaves exposed to UV-B radiation

Abstract: Ultraviolet-B radiation acts as an environmental stimulus, but in high doses it has detrimental effects on plant metabolism. Plasma membranes represent a major target for Reactive Oxygen Species (ROS) generated by this harmful radiation. Oxidative reactions occurring in the apoplastic space are counteracted by antioxidative systems mainly involving ascorbate and, to some extent, glutathione. The occurrence of the latter and its exact role in the extracellular space are not well documented, however. In Arabidop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…(A) Number of CWPs identified in experiment 1 (1DE) vs. number of CWPs identified in experiment 2 (shotgun). (B) Comparison of the number of CWPs identified in this study (destructive method) and in previous studies (non‐destructive method) . (C) Distribution (%) of CWPs identified in the overall rosette cell wall proteome (non‐destructive and destructive methods) in functional classes according to bioinformatic prediction of functional domains: PAC (proteins acting on carbohydrates), OR (oxido‐reductases), P (proteases), LM (proteins possibly related to lipid metabolism), ID (proteins with interactions domains with carbohydrates or proteins), S (proteins possibly involved in signaling), SP (structural proteins), M (miscellaneous proteins), UF (proteins of yet unknown function).…”
Section: Number Of Proteins Specific To the Enlarged Rosette Cell Walmentioning
confidence: 86%
“…(A) Number of CWPs identified in experiment 1 (1DE) vs. number of CWPs identified in experiment 2 (shotgun). (B) Comparison of the number of CWPs identified in this study (destructive method) and in previous studies (non‐destructive method) . (C) Distribution (%) of CWPs identified in the overall rosette cell wall proteome (non‐destructive and destructive methods) in functional classes according to bioinformatic prediction of functional domains: PAC (proteins acting on carbohydrates), OR (oxido‐reductases), P (proteases), LM (proteins possibly related to lipid metabolism), ID (proteins with interactions domains with carbohydrates or proteins), S (proteins possibly involved in signaling), SP (structural proteins), M (miscellaneous proteins), UF (proteins of yet unknown function).…”
Section: Number Of Proteins Specific To the Enlarged Rosette Cell Walmentioning
confidence: 86%
“…The several PR-1 proteins, despite their unknown biological functions, are often used as markers of biotic stress [20,71], but in this review they were also found in abiotic stress and the non-challenged conditions [12,19,37,72,73]. All PR-1 proteins have similar structure and are classified in the same family on the basis of sequence homology although they can have different properties and differ substantially in biological activity [64].…”
Section: The Biological Processes Detected In the Ecsmentioning
confidence: 99%
“…In poplar and Arabidopsis this protein was found together with a cysteine-rich repeat secretory protein 38-like which seems to be structurally similar with a lipid transfer protein from tomato and can, thus, be classified as a PR-14 protein [21,73]. …”
Section: The Biological Processes Detected In the Ecsmentioning
confidence: 99%
See 2 more Smart Citations